An analysis of magic realism in midnight's children (Salman Rushdie) and the famished road (Ben Okri) - Faridatul Mastura, Mohamed Khatib (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to analyze magic realism in which the foci are to examine the characteristics of magic realism as listed by Faris (1998) and the usage of magic realism by the authors in emphasizing the effects of colonization. The texts used are Midnight’s Children and The Famished Road; written by magic realist writers; Salman Rushdie and Ben Okri. Data collection is done through literature research using the theoretical framework of magic realism. The theoretical framework of magic realism is a combination of the poetics of magic realism by Faris (1998) and cultural theory by Jacobsen (2005). The result of this study shows that magic realism has its effects on colonization and magic realism is perceived as decolonizing device. The findings of this study bridge the existing knowledge gap noted from related previous studies.